THE INFLUENCE OF USING STORIES TOWARDS STUDENTS‟ GRAMMAR MASTERY AT THE SECOND SEMESTER OF TENTH CLASS AT MA AL-HIKMAH BANDAR LAMPUNG - Wahyuningsih, Sri (LPPM STKIP PGRI Bandar Lampung, 2015)
The objective of teaching and learning English as a foreign Language is to enable the students to communicate in English both in oral and written. In making sentences or express an idea in oral or writing, the students have to master grammar. Grammar is greatly needed and has important roles in making correct sentences. Without mastering grammar, we can not arrange the senteces in correct one by speaking or writing. In this research the writer did research about using stories towards students‟ grammar mastery.The population of the research was the students at the second semester of tenth class at MA Al-Hikmah Bandar Lampung. The writer took two classes as the sample, they are; X B as class experimental class and X C as control class. In the experimental class, there are 36 students and the second one there are 35 students, so the total of experimental and control class is 71. In taking the sample the writer used random sampling technique. In collecting the data, the writer used objective test that were multiple choice test. The test consisted of 50 items and each item consisted of 5 options.The result of the research showed that the hypothesis test by using = 3.01 and from the distribution table of the distribution table of the significance level 5 % known = (1 − 1/2. = 1.98 and = ( 1 – ) = 1.66. The level of 1 % know = (1 − 1/2. = 2.62 and = ( 1 – ) = 2.36. It means that > . So it can be said that there is the influence of using stories towards students grammar mastery at the second semester of the tenth class at MA Al-Hikmah Bandar Lampung and the average score of the students‟ grammar mastery who were taught by using stories was higher than those who were taught by using grammatical method.